Design, synthesis and structure-activity relationship studies of 3-phenylpyrazino[1,2-a]indol-1(2H)-ones as amyloid aggregation and cholinesterase inhibitors with antioxidant activity - Sarbjeet Singh Gujral; Arash Shakeri; Leila Hejazi; Praveen P.N. Rao (Elsevier, 2022)
A group of novel fused tricyclic derivatives based on a pyrazino[1,2-a]indol-1(2H)-one ring scaffold possessing a C3 phenyl substituent were designed, synthesized and evaluated as multi-target-directed-ligands (MTDLs) for Alzheimer's disease (AD). The biochemical assays were carried out to determine their inhibition activity toward i) amyloid peptide aggregation (Aβ40 and Aβ42), ii) acetyl and butyrylcholinesterase (AChE and BuChE) enzyme inhibition and iii) evaluation of their antioxidant properties. These studies identified several 3-phenylpyrazino[1,2-a]indol-1(2H)-one derivatives that exhibited multi-targeting activity capable of preventing amyloid aggregation (Aβ40 and Aβ42 inhibition range ​= ​10-89.5% at 25 ​μM), inhibition of cholinesterase enzymes (AChE and BuChE IC50 range ​= ​1.6-21 ​μM) and antioxidant activity (24-55% inhibition at 25 ​μM). The lead compound 5i (3-(3,4-dimethoxyphenyl)pyrazino[1,2-a]indol-1(2H)-one), exhibited multi-targeting activity with excellent inhibition of Aβ40 and Aβ42 aggregation (85% and 90% inhibition at 25 ​μM), dual inhibition of human cholinesterase enzymes (hAChE IC50 ​= ​7.5 ​μM; hBuChE IC50 ∼ 15 ​μM) and antioxidant property (∼39% inhibition at 25 ​μM). Compound 5i did not exhibit toxicity in mouse HT22 mouse hippocampal neuronal cells at 25 ​μM. In addition, 5i was able to prevent Aβ42 mediated cytotoxicity in the mouse hippocampal neuronal HT22 ​cells (77% cell viability). In the in vitro PAMPA-BBB permeation assay, compound 5i and 5a showed permeability values Pe ​= ​2.25 ​× ​10−6 ​cm/s and 6.20 ​× ​10−6 ​cm/s respectively, suggesting their ability to get into brain. These structure-activity studies demonstrate that the fused tricyclic pyrazino[1,2-a]indol-1(2H)-one template is capable of binding to Aβ (Aβ40 and Aβ42), and human cholinesterase enzymes (hAChE and hBuChE), and that a C3 3,4-diOMe-phenyl is a novel Aβ-binding pharmacophore that can be incorporated in the design of anti-AD agents.